Optoelectronic properties of GaAs nanowire photodetector - Wang, H; Parkinson, P; Tian, J; Saxena, D; Mokkapati, S; Gao, Q; Prasai, P; Fu, L; Karouta, F; Tan, H; Jagadish, C (2012)
A single GaAs nanowire (NW) photodetector (PD) is fabricated based on the back-to-back Schottky diode structure. Optoelectronic properties are characterized by measuring device photocurrent, and also the spectral response, which indicates our device is very sensitive and applicable as a PD. © 2012 IEEE.